SR141716A induces in rats a behavioral pattern opposite to that of CB1 receptor agonists. - Costa Barbara; Colleoni Mariapia (Acta Pharmacologica Sinica, 2016)
AIM: To examine the acute actions of the CB1 cannabinoid receptor antagonist SR141716A [N-piperidino-5-(4-chlorophenyl)- 1-(2,4-dichlorophenyl)-4-methylpyrazole-3-carboxamide] on typical behavioral pattern of psychoactive cannabinoids in rats. METHODS: At different time after injection the tail-flick response latency, the rectal temperature, the locomotor activity, and the immobility on a ring as well as the numbers of rears, self-grooming episodes (lasting 5 s), and fecal pellets were measured. RESULTS: Acute administration of SR141716A (3 mg/kg i.p.) induced a significant increase in horizontal locomotor activity assayed by an activity meter, in stereotypic activity (such as rearing and self-grooming) and in defecation, and a decrease in nociceptive threshold recorded as tail-flick latency. This dose had no effect on ring immobility and did not change the body temperature. CONCLUSION: These results demonstrate that this cannabinoid antagonist itself was inducing behavior opposite to that of CB1 receptor agonists.